Preparation method of spherical high-entropy carbide powder and SiC / high-entropy carbide coating

Spherical high-entropy carbide powder was prepared by atmospheric pressure carbothermal reduction and spray drying technology, and a SiC transition layer was generated in situ on the substrate. This solved the problems of insufficient preparation of high-entropy carbide powder and coating performance, and realized a composite coating with high density and good interfacial bonding, which is suitable for high-temperature protection in aerospace and other fields.

CN121248296APending Publication Date: 2026-01-02HEBEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511526407.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-24
Publication Date
2026-01-02

AI Technical Summary

Technical Problem

Existing methods for preparing high-entropy carbide powders require vacuum or protective atmosphere equipment, which is costly, energy-intensive, and produces powders with irregular morphology, making large-scale production difficult. Furthermore, the coatings lack density and interfacial bonding strength, making it difficult to meet high-temperature protection requirements.

Method used

Spherical high-entropy carbide powder was prepared by atmospheric pressure carbothermal reduction combined with spray drying technology. A high-density SiC/high-entropy carbide composite coating was prepared by generating a dense SiC transition layer in situ on the substrate and using atmospheric plasma spraying process.

Benefits of technology

It has enabled the preparation of spherical high-entropy carbide powders that are low-cost and easy to mass-produce, significantly improving the density and interfacial bonding performance of the coating and meeting the high-temperature protection requirements of aerospace and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121248296A_ABST
    Figure CN121248296A_ABST
Patent Text Reader

Abstract

The invention relates to spherical high-entropy carbide powder and a preparation method of a SiC / high-entropy carbide coating. According to the method, normal-pressure carbon thermal reduction synthesis of high-entropy carbides is realized in a common box-type furnace and in an air atmosphere through a local atmosphere isolation structure of'laying graphite paper, upper graphite powder and covering activated carbon ', then a compact SiC transition layer is generated in situ on a substrate by utilizing a two-step method of'plasma spraying of a pure silicon layer and then high-temperature embedding carburization', and the high-entropy carbide is prepared. And finally, the high-entropy carbide coating is prepared through a thermal spraying method. The process is simple, the cost is low, large-scale preparation is easy, the high-temperature wear resistance and the ablation resistance of the coating can be remarkably improved, and the harsh requirements of the aerospace field and the like for the ultra-high-temperature protective coating are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of advanced ceramic materials technology, specifically relating to a method for preparing high-entropy carbide powder and a SiC / high-entropy carbide composite coating. More specifically, it relates to a technique that combines a box furnace carbothermal reduction method with spray drying technology to prepare spherical high-entropy carbide powder, prepares a SiC transition layer through in-situ carburizing, and uses the spherical high-entropy carbide powder to prepare a high-density, high-performance high-entropy carbide coating through a thermal spraying process. Background Technology

[0002] High-entropy carbides are novel ceramic carbide materials composed of four or more metallic elements in near equimolar ratios. Due to their high-entropy effect, lattice distortion effect, hysteresis diffusion effect, and "cocktail" effect, high-entropy carbides exhibit superior properties far exceeding those of traditional binary carbides, including ultra-high hardness, excellent high-temperature structural stability, wear resistance, and corrosion resistance. These properties make them promising for applications in protective coatings for extreme environments, cutting tools, and aerospace hot-end components. In particular, the ultra-high temperature hot-load areas of hypersonic vehicles (such as tail nozzles, air intake lips, wing leading edges, and nose cones) must withstand prolonged exposure to high-temperature airflow at 1700–2200 °C during service. These components not only bear extreme thermal and mechanical loads but must also maintain structural integrity and resistance to oxidation and ablation at high temperatures. Therefore, developing novel ultra-high temperature protective materials capable of long-term stable operation in environments ≥1700 °C has become one of the key bottlenecks in the development of hypersonic technology. High-entropy carbides are widely recognized as one of the most promising candidate materials due to their tunable composition, highly stable phase structure, and excellent high-temperature mechanical properties.

[0003] However, the practical transformation of high-entropy carbide materials from powder synthesis to coating applications still faces two major technical challenges, which seriously hinder their engineering application process: (1) Challenges in large-scale, low-cost powder preparation: Existing technologies involve high-temperature solid-state reaction methods under vacuum or protective atmospheres (as reported in "Scripta Materialia, 2019, 162: 90-93" and "Journal of Materials Science & Technology, 2021, 72: 23-28"). The main steps of this technology are: mixing metal oxides with a carbon source and then carrying out a long-term carbothermic reduction reaction at a high temperature of >2000 ℃ under vacuum or inert atmosphere. The limitations of this technology are: it must rely on expensive vacuum or atmosphere protection equipment, which requires large equipment investment, consumes a lot of energy, has a long preparation cycle, and the resulting powder has irregular morphology and poor flowability, making it difficult to meet the requirements of thermal spraying processes for feed powder, which seriously hinders its large-scale production and application.

[0004] (2) Densification and interfacial bonding issues of coatings: Existing technologies for preparing high-entropy carbide coatings include the scheme disclosed in patent CN118530024A. The main steps of this technology are: using radio frequency induction plasma to spheroidize high-entropy carbide powder to obtain spherical powder, and then using supersonic plasma spraying technology to deposit the coating.

[0005] The limitations of this technology are as follows: radio frequency plasma spheroidization equipment is complex and costly, resulting in poor economic efficiency; furthermore, even when using spherical powders, the high-entropy carbide coatings obtained by direct spraying still suffer from high porosity and insufficient density, while the bonding strength between the coating and the substrate needs further improvement. Overall, existing high-entropy carbide coating preparations still have significant shortcomings in terms of thickness, density, and interfacial bonding. While thermal spraying methods are highly efficient, they are limited by powder properties, requiring extremely high heat source power for direct spraying of high-entropy carbides, and the coating porosity remains high. Therefore, how to improve the sprayability of powder while simultaneously enhancing the density and strong bonding with the substrate has become a pressing issue for the practical application of high-entropy carbide protective coatings.

[0006] In view of the shortcomings of the existing technology, there is an urgent need to provide a new solution with a simple process route, low cost and suitability for large-scale production, in order to prepare high-entropy carbide powder with regular morphology and significantly improve the density and interfacial bonding performance of ceramic coatings prepared from the powder.

[0007] In summary, the preparation methods for high-entropy carbide powders and coatings generally suffer from the following drawbacks: (1) Powder preparation requires special conditions such as vacuum, protective atmosphere or high-energy ball milling, which makes it difficult to produce on a large scale; (2) Coatings prepared by methods such as sputtering are thin and have limited protective effect on the substrate. Thermal spraying is a highly efficient method for preparing coatings with high deposition rates, but due to the poor fluidity and difficulty in melting of high-entropy carbide powders, direct spraying often requires extremely high power and the coating density is not ideal.

[0008] Therefore, there is an urgent need for a new solution that simplifies the process, reduces costs, produces powders with regular morphology, and can significantly improve the density and bonding performance of the coating. Summary of the Invention

[0009] This invention aims to overcome the shortcomings of existing technologies in the preparation of high-entropy carbide powder and coating performance, and provides a method for preparing spherical high-entropy carbide powder and SiC / high-entropy carbide coatings. This method utilizes a local atmosphere isolation structure of "laying graphite paper + top graphite powder (slightly compacted) + covering with activated carbon," making it possible to achieve atmospheric pressure carbothermal reduction synthesis of high-entropy carbides in a conventional box furnace under air atmosphere. Subsequently, a two-step method of "first plasma spraying a pure silicon layer, then high-temperature embedding and carburizing" is used to generate a dense SiC transition layer in situ on the substrate. This invention features a simple process, low cost, and ease of large-scale preparation, significantly improving the coating's high-temperature wear resistance and ablation resistance, meeting the stringent requirements of aerospace and other fields for ultra-high temperature protective coatings.

[0010] This invention provides the following technical solution: A method for preparing spherical high-entropy carbide powder includes the following steps: S1. Raw material preparation: Select the corresponding metal oxide powder according to the chemical formula of the target substance MC, and calculate the weight according to the equimolar ratio of metal atoms; in addition, determine the required carbon source mass according to the sum of the molar amounts of the corresponding metal carbides; finally, mix the metal oxide powder and carbon source to obtain the raw material powder. Wherein, M is at least four of the metals Ta, Hf, Nb, Ti, V, Mo, Zr and W; and the molar ratio of each metal element is the same; the carbon source is selected from at least one of carbon black, graphite and carbon nanotubes; the metal oxide powder is Ta2O5, HfO2, Nb2O5, TiO2, V2O5, MoO3, ZrO2 and WO3 of the corresponding metal; The metal oxide powder has a particle size of 0.001~10 μm, and the carbon source has a particle size of 0.001 μm~10 μm.

[0011] S2. Ball milling and mixing: Add the raw material powder prepared in step S1 into a ball mill and mix evenly. The ball-to-material ratio is 1~2:1, the rotation speed is 100~300 r / min, and the ball milling is carried out for 1~3 hours to obtain ball milled powder. S3. Carbothermic reduction synthesis: The inside of the crucible is lined with graphite paper, and the uniformly mixed raw material powder is loaded into the crucible; graphite paper is then placed on top of the powder; a 5-10 mm layer of graphite powder is then laid on the graphite paper and flattened using a flat press block; finally, a layer of activated carbon with a particle size of 1-5 mm is placed on top, with a covering thickness of 10-20 mm; after the crucible is covered, it is placed in a box furnace and heated at 1500-1800 ℃ for 0.5-2 hours. After the reaction is completed, it is cooled with the furnace to obtain high-entropy carbide powder; Preferably, the heating rate is 2~10 ℃ / min, which is beneficial to obtaining a uniform carbide phase.

[0012] S4. Grinding and refining: The high-entropy carbide powder obtained in step S3 is ball-milled (ball-to-material ratio 2~5:1, rotation speed 200~400 r / min) for 1~2 hours using intermittent ball milling to break up agglomerates and refine particle size to obtain high-entropy carbide powder with a particle size of less than 10 μm. In intermittent ball milling, the machine is stopped for 5 to 15 minutes to cool down after every 15 to 25 minutes of grinding.

[0013] S5. Spray granulation: The refined powder is mixed with deionized water, binder and dispersant in proportion to form a uniform slurry, and then the slurry is granulated by spray drying to obtain spherical high-entropy carbide powder. Preferably, the binder is a 1-3 wt.% sodium carboxymethyl cellulose solution or a polyvinyl alcohol aqueous solution, the dispersant is sodium polyphosphate (accounting for 1-2 wt.% of the total powder mass), and the slurry solid content is 30-40 wt.%; the spray drying inlet temperature is 240-260 ℃, and the outlet temperature is 100-120 ℃.

[0014] The high-entropy carbide powder prepared by the above method is a regular spherical or near-spherical shape with a particle size D50 adjustable from 30 to 70 μm, uniform particle size distribution, Hall flowability <45 s / 50 g, and loose packing density ≥2.4 g / cm³. 3 Furthermore, it exhibits a uniform composition with a single rock salt structure phase. This spherical high-entropy carbide powder is particularly suitable as a feed material for processes such as thermal spraying.

[0015] A method for preparing a high-density SiC / high-entropy carbide composite coating includes the following steps: S6. Pretreatment of substrate before spraying: Roughen the surface of the substrate and grind it to a surface roughness Ra≈2~4 μm; The matrix material is graphite, carbon fiber reinforced carbon matrix composite, carbon fiber reinforced silicon carbide matrix composite, or silicon carbide fiber reinforced silicon carbide matrix composite. S7. Preparation of SiC transition layer: A SiC transition layer is prepared on the surface of the pretreated substrate using thermal spraying technology; The thermal spraying technology mentioned is atmospheric plasma spraying or supersonic flame spraying; When performing deposition for atmospheric plasma spraying or supersonic flame spraying processes, a pure silicon coating of 50-100 μm thickness is first deposited on the substrate surface by atmospheric plasma spraying; the substrate is preheated to 100-200 ℃ before spraying to improve the smoothness and adhesion of the coating. The atmospheric plasma spraying process parameters include: current 450~550 A, voltage 60~80 V, argon flow rate 90~120 L / min, hydrogen flow rate 80~120 L / min, and powder delivery gas flow rate 0.1~0.3 m³ / min. 3 / h, spray gun distance from surface 50~100 mm; then, place the substrate specimen with pure silicon coating in a corundum crucible with graphite paper wrapped inside, completely encapsulate the substrate in graphite powder and compact it; after covering the crucible with the lid, place the crucible in a box furnace and hold at 1450~1550 ℃ for 0.5~2 hours to carry out carburizing reaction. After the furnace cools to room temperature, take out the specimen, and a dense SiC transition layer is generated in situ on the substrate surface; the obtained SiC transition layer is about 50~100 μm thick and is firmly bonded to the substrate; after carburizing, the surface of the SiC layer can be lightly sandblasted to increase its roughness Ra to 6~8 μm, providing a good bonding interface for subsequent coating deposition.

[0016] S8. Preparation of high-entropy carbide coating: A high-entropy carbide ceramic coating is deposited on the SiC transition layer using thermal spraying technology, and the spray feed is the spherical high-entropy carbide powder described above; Deposition is carried out using atmospheric plasma spraying or supersonic flame spraying processes, with the substrate preheated to 100~200 ℃ during spraying.

[0017] The atmospheric plasma spraying process includes: a current of 450~550 A, a voltage of 75~90 V, a main gas Ar flow rate of 80~130 L / min, an auxiliary gas H2 flow rate of 90~130 L / min, and a powder delivery gas flow rate of 0.3~0.6 m³ / min. 3 / h, spray gun distance from substrate 80~150mm. By adjusting process parameters, the coating thickness can reach 200~300 μm.

[0018] The high-entropy carbide ceramic layer prepared by spraying is metallurgically bonded to the underlying SiC transition layer to form an integral SiC / high-entropy carbide composite coating.

[0019] According to the above preparation method, a SiC transition layer with a thickness of 50-100 μm and a high-entropy carbide ceramic coating with a thickness of several hundred micrometers can be obtained on the surface of a graphite or carbon fiber reinforced carbon-based composite matrix. Testing showed that the composite coating of this invention has a density >95% and a porosity <5%, exhibiting a highly dense microstructure.

[0020] The essential features of this invention are: This invention addresses the technical bottlenecks in the powder preparation and coating applications of high-entropy carbide materials, proposing several innovative solutions that offer significant differences and advantages compared to existing technologies: This invention presents a novel atmospheric pressure carbothermal reduction powder preparation process: By designing a specially crafted crucible atmosphere isolation structure (raw material powder + graphite paper + compacted graphite powder + covering activated carbon), a multi-layered structure is used to gradually adsorb and filter air (oxygen, etc.), creating a localized strong reducing atmosphere within the air environment of a standard box furnace. This achieves the carbothermal reduction synthesis of high-entropy carbide powder without requiring the high vacuum or inert atmosphere equipment relied upon in traditional processes. This innovation significantly simplifies equipment requirements, reduces energy consumption and costs, and improves preparation efficiency. Combined with spray drying technology, the resulting spherical high-entropy carbide powder exhibits uniform particle size distribution and a Hall flow rate <45 s / 50 g, significantly improving feed flowability and meeting the requirements of thermal spraying processes, overcoming the problems of poor powder flowability and low spray deposition efficiency inherent in traditional methods.

[0021] In-situ construction of SiC transition layer: A dense SiC transition layer is generated in-situ on the substrate surface using a process of "first plasma spraying of silicon layer - then high-temperature embedding and carburizing". Compared with the direct spraying of high-entropy carbides, which is prone to peeling off due to thermal stress, the SiC transition layer has a strong bond with the substrate, which can alleviate stress concentration caused by thermal expansion mismatch and significantly improve the bonding strength between the coating and the substrate.

[0022] Preparation of High-Density Composite Coating: Using the aforementioned spherical high-entropy carbide powder, a high-density (>95%) SiC / high-entropy carbide composite protective coating was successfully prepared on a SiC transition layer via atmospheric plasma spraying or supersonic flame spraying. This composite coating overcomes the shortcomings of existing high-entropy carbide direct-spray coatings, which suffer from high porosity and low density. The coating thickness can reach hundreds of micrometers, exhibiting high hardness and excellent wear resistance and ablation resistance. Under the same working conditions, the density, hardness, and ablation resistance of the coating of this invention are significantly superior to traditional single or multi-component carbide ceramic coatings.

[0023] The beneficial effects of this invention are as follows: (1) Atmospheric pressure carbothermic reduction reduces equipment and costs: By designing a crucible atmosphere isolation structure, the carbothermic reduction synthesis of high-entropy carbides can be completed in a conventional box furnace. This eliminates the need for complex equipment such as vacuum furnaces, protective atmosphere furnaces, or plasma spheroidization, significantly reducing equipment investment and operating costs for powder preparation. Combined with conventional spray drying processes, high-performance spherical high-entropy carbide powders can be directly obtained, greatly simplifying the process flow, shortening the preparation cycle, reducing energy consumption, and avoiding the introduction of impurities. The method of this invention does not require expensive special environmental control equipment; it can achieve batch preparation of high-entropy carbide powders using conventional box furnaces and spray drying devices, demonstrating promising prospects for industrial application.

[0024] (2) In-situ SiC transition layer enhances interfacial bonding: A dense SiC transition layer is constructed on the substrate surface using the method of "first spraying a silicon layer, then in-situ carburizing". This transition layer is firmly bonded to the substrate, effectively buffering the stress caused by the difference in thermal expansion coefficients, improving the stability of the coating under ablation conditions, and making it less prone to peeling. Experiments have shown that after introducing the SiC transition layer, the adhesion strength between the high-entropy carbide coating and the substrate is significantly improved, effectively improving the problem of cracking and peeling caused by insufficient bonding force when directly spraying high-entropy carbide coatings.

[0025] (3) High-density, wear-resistant, and ablation-resistant composite coating: The spherical high-entropy carbide powder prepared in this invention has uniform element distribution, single-phase purity, and good fluidity, ensuring stable deposition during the thermal spraying process. Therefore, even using conventional atmospheric plasma spraying technology, a high-entropy carbide ceramic coating with a density >95% and a porosity <5% can be obtained. More importantly, through the coating structure design of "SiC transition layer + high-entropy carbide ceramic surface layer", the resulting composite coating is significantly superior to existing single carbide or multi-component carbide coatings in key indicators such as nano-hardness, wear resistance, and ablation resistance. Test results show that the average friction coefficient of the coating of this invention under test conditions of 5 N load, 350 r / min rotation speed, and corundum grinding ball is 0.4~0.6, and the wear rate is 10 -7 ~10 -6 Range. At a heat flux of 4.02 MW / m². 2 After being ablated for 120 s in a plasma jet at a temperature greater than 2400 ℃, the coating remained intact without large-area peeling. These properties far surpass those of comparative coatings (such as TiC single-phase coatings or (ZrTi)C multi-component carbide coatings), demonstrating the outstanding advantages of the high-entropy carbide composite coating of this invention in the field of high-temperature wear resistance and ablation resistance. Attached Figure Description

[0026] Figure 1 Schematic diagram of the interior of the corundum crucible for preparing high-entropy carbide powder in a box furnace Figure 2 The images show SEM images, particle size distribution, and elemental composition of the spherical high-entropy carbide (TaNbTiVMo)C powder obtained in Example 1.

[0027] Figure 3 The XRD pattern of the (TaNbTiVMo)C powder obtained in Example 1. Figure 4 The images show the XRD patterns of the SiC transition layer and the high-entropy carbide (TaNbTiVMo)C coating obtained in Example 1, as well as the SEM image of the graphite matrix / SiC / (TaNbTiVMo)C composite coating. Figure 4 (a) XRD pattern of the SiC transition layer; Figure 4 (b) XRD pattern of (TaNbTiVMo)C coating; Figure 4 (c) is a SEM image of the SiC / (TaNbTiVMo)C composite coating; Figure 5 The images shown are SEM images of the surface morphology of the worn area and the wear track contour image of the (TaNbTiVMo)C coating obtained in Example 1 after wear. Figure 5 (a) is a SEM image of the wear area; Figure 5 (b) is a contour diagram of the wear marks; Figure 6 The macroscopic morphology of the (TaNbTiVMo)C coating obtained in Example 1 after plasma ablation for different times. Detailed Implementation

[0028] The present invention will now be described in detail with reference to specific embodiments.

[0029] The preparation of the material quantity in this invention is as follows: select the corresponding metal oxide powder according to the chemical formula of the target substance MC, and calculate the weight according to the equimolar ratio of metal atoms; in addition, determine the required carbon source mass according to the sum of the molar amounts of the corresponding metal carbides. The method for weighing the carbon source, taking a typical carbothermic reduction reaction as an example, has the general formula: MOx + (x+1)C → MC + xCO↑, where MOx represents any metal oxide. During calculation, for each metal oxide, the amount of carbon required for its complete reduction and carbonization must be calculated individually based on its own stoichiometric ratio. Then, the raw materials are mixed to obtain the powder. Example 1: Preparation of spherical (TaNbTiVMo)C high-entropy carbide powder and coating S1. Using Ta₂O₅, Nb₂O₅, TiO₂, V₂O₅, MoO₃ powders and carbon black as raw materials, firstly, based on the principle of equimolar amounts of the five metal elements in the target high-entropy carbide (TaNbTiVMo)C, the required molar ratio of each metal oxide is calculated. Subsequently, based on the stoichiometric ratio required for the complete carbothermic reduction reaction, the theoretical carbon content is calculated. The mass percentage is Ta₂O₅:Nb₂O₅: TiO₂: V₂O₅: MoO₃: C = 25.32: 15.23: 9.15: 10.42: 16.50: 23.38.

[0030] S2. Raw material mixing: Place the prepared raw material powder in a high-speed grinder, using zirconia balls as the grinding media (grind ball size is 5-10 mm), with a ball-to-material ratio of 2:1. Grind the powder at a speed of 200 r / min for 1 hour to ensure that all components are fully and uniformly mixed.

[0031] S3. Carbothermic Reduction Synthesis: The inside of the crucible is lined with graphite paper to separate the inner wall. The mixed powder obtained in S2 is loaded into the graphite-paper-lined corundum crucible, with graphite paper covering the powder to prevent contamination. Then, graphite powder (lightly pressed with a flat block to a thickness of approximately 5 mm) is spread on the graphite paper, and finally, a layer of activated carbon (1-5 mm particle size) is placed on top (20 mm thick) to create a localized reducing atmosphere. The crucible is then covered and placed in a box furnace. The temperature is increased to 1500 °C at a rate of 5 °C / min (to obtain a uniform carbide phase) and held for 1 hour for the carbothermic reduction reaction. After the reaction is complete, the furnace is cooled to complete the carbothermic reduction reaction, ultimately yielding an irregularly shaped high-entropy carbide powder.

[0032] S4. Ball Milling: The powder obtained in S3 is rapidly ground and crushed using a high-speed grinder with a ball-to-particle ratio of 3:1 at a speed of 300 r / min. The grinding is stopped for 10 min every 20 min to prevent overheating. The total grinding time is 1 hour to break up agglomerates and refine particle size, obtaining high-entropy carbide refined powder with a particle size of less than 10 μm.

[0033] S5. Preparation of spherical high-entropy carbide powder: The refined powder obtained in S4 was mixed with deionized water, sodium carboxymethyl cellulose aqueous solution (prepared by dissolving sodium carboxymethyl cellulose in deionized water to a concentration of 1.3 wt.%, and heating and stirring in an 80 ℃ water bath for 2 hours), and sodium polyphosphate (added at 1 wt.% of the mass of the refined powder), and stirred to form a uniform slurry with a solid content (refined powder) of 35 wt.%. During spray drying, the inlet temperature was set to 250 ℃ and the outlet temperature to 120 ℃. The slurry was conveyed into the atomizer by a peristaltic pump (feed rate 130 mL / min). The slurry was centrifuged by the atomizer to form droplets, which were heated and dried in the drying chamber to form spherical high-entropy carbide powder, which was collected in the bottom tank. The granulated product was collected and sieved to obtain spherical (TaNbTiVMo)C powder with a particle size distribution of 40~60 μm. The powder was tested and found to have a Hall flow rate of 40.0 s / 50 g and a loose packing density of 2.5 g / cm³. 3 The flowability test of the powder was conducted in accordance with GB / T39696-2020.

[0034] Figure 1 This is a schematic diagram of the interior of the corundum crucible used in the box furnace of this invention for preparing high-entropy carbide powder. It shows the arrangement of the graphite paper separator layer, compacted graphite powder, and activated carbon inside the corundum crucible.

[0035] Figure 2The image shows SEM images of the spherical high-entropy carbide (TaNbTiVMo)C powder prepared by the method of this invention in Example 1, demonstrating its good sphericity and uniform particle size distribution. In the image, (ac) are SEM images of the surface morphology of the spherical powder at different magnifications; (d) is a SEM image of the cross-section of the spherical powder; (e) is a particle size distribution diagram of the spherical powder; and (f) shows the elements and their contents at section A. The elemental content includes five metallic elements, which is within the elemental content range of high-entropy carbides.

[0036] Figure 3 The X-ray diffraction pattern of the (TaNbTiVMo)C powder prepared in Example 1 shows that it has a single Fm-3m rock salt structure.

[0037] S6. Pretreatment of the substrate before spraying: The surface of the graphite substrate is roughened, preferably by sanding with 100-grit sandpaper until the surface roughness Ra is about 4 μm.

[0038] S7. Preparation of SiC Transition Layer: A pure silicon layer with a thickness of approximately 100 μm was deposited on the roughened graphite substrate using atmospheric plasma spraying technology. The spraying parameters were: current 500 A, voltage 80 V, argon (Ar) flow rate 100 L / min, hydrogen (H2) flow rate 100 L / min, and powder feed gas flow rate 0.2 m³. 3 / h, the spray gun is 50 mm away from the substrate surface. After spraying, the sample is placed in a corundum crucible, the substrate is completely covered in graphite powder and compacted, and the crucible wall is isolated with graphite paper. Carburizing reaction is carried out in a box furnace at 1500℃ for 1 h. After cooling with the furnace, it is taken out to obtain the SiC transition layer. Then, it is lightly sandblasted, and the roughness after sandblasting is 6-8 μm.

[0039] S8. Preparation of High-Entropy Carbide Coating: Spherical (TaNbTiVMo)C powder was used as feedstock and sprayed onto a graphite substrate containing a SiC transition layer using atmospheric plasma spraying technology. Main parameters: Power 40 kW, Current 500 A, Voltage 80 V, Main gas (Ar) flow rate 90 L / min, Auxiliary gas (H2) flow rate 100 L / min, Powder feed gas flow rate 0.4 m³ / min. 3 / h, spraying distance 100mm, thickness greater than 200 μm.

[0040] Figure 4Example 1 shows the XRD pattern and cross-sectional SEM image of the SiC / (TaNbTiVMo)C composite coating prepared in Example 1 of this invention. The XRD pattern indicates that the main phase of the SiC transition layer is α-SiC, and the high-entropy carbide coating is mainly composed of the (TaNbTiVMo)C phase with an FCC structure. The cross-sectional SEM image shows that the thickness of the SiC transition layer is approximately 100 μm, and the thickness of the high-entropy carbide coating reaches over 200 μm, indicating that the composite coating has high density. Figure 5 The images show the surface morphology and wear track profile of the high-entropy carbide composite coating after wear. The surface wear resulted in the formation of a dense film, which helps to reduce wear. Figure 6 The surface morphology of the high-entropy carbide composite coating after plasma ablation for different times is shown. The evolution of the coating's surface morphology at different times under plasma ablation conditions of 2400 ℃ is illustrated. This coating maintained its structural integrity and showed no large-area peeling under plasma ablation conditions of 2400 ℃ for 120 s, indicating good ablation resistance. Image analysis revealed that the coating's density was greater than 95%, porosity less than 5%, and nanohardness reached 23.96 GPa. The coefficient of friction was 0.4, and the wear rate was 3.9 × 10⁻⁶. -7 mm 3 / N•m. After 120 s of plasma ablation, the linear ablation rate was only -1.09 μm / s, and the mass ablation rate was 0.41 mg / s. Furthermore, compared with coatings obtained by atmospheric plasma spraying of TiC, ZrC-TiC, and ZrC-TiC-NbC-Cr3C2-V8C7 powders, the SiC / high-entropy carbide ceramic composite coating prepared by thermal spraying in this invention exhibits higher density, hardness, wear resistance, and ablation resistance.

[0041] The nanoscale hardness, wear rate, and linear ablation rate of the SiC / high-entropy carbide ceramic composite coating prepared in Example 1 of this invention are compared with those of the top high-entropy carbide ceramic layers prepared by the same process: single-principal-element carbide TiC coating (prepared by spraying TiC powder), dual-principal-element carbide (ZrTi)C coating (prepared by spraying ZrC-TiC spherical powder), and high-entropy carbide (ZrNbTiCrV)C coating (prepared by directly spraying ZrC-TiC-NbC-Cr3C2-V8C7 spherical powder). The results are shown in Table 1.

[0042] The nanohardness of the polished ceramic coating surface was characterized using a Hysitron TI Premier nanoindenter. The load was 10 mN, and 10 test points were taken for each sample. To avoid size effects and mutual interference between indentations, a certain spacing was maintained between the indentations. The final result was the average of the 10 test values. The tribological properties of the coating were tested using an SFT-2M ball-disc tribological testing machine. Test conditions: load 5 N, rotation speed 350 r / min, 4 mm diameter corundum balls, and loading time 30 min. The ablation resistance of the coating was tested using a ZB-80 plasma spraying system. Plasma jet ablation conditions: ablation distance of 50 mm, temperature above 2400 ℃, and heat flux of 4.02 MW / m². 2 The ablation time was 120 s. It can be seen that the high-entropy carbide ceramic coating prepared by the method of this invention has better wear resistance and ablation resistance compared with single-principal-element carbide TiC, multi-principal-element carbide (ZrTi)C, and high-entropy carbide (ZrNbTiCrV)C coatings obtained by direct carbide spraying. For ease of comparison, the coating performance parameters of Example 1 and each comparative example are listed in Table 1. The negative sign indicates that a protective oxide layer is formed on the surface during the ablation process, resulting in localized surface bulging or increased thickness.

[0043] Table 1 Comparison of coating performance parameters between Example 1 and comparative examples

[0044] Note: Percentages represent the improvement (for nanohardness) or decrease (for wear rate and linear ablation rate) compared to Comparative Examples 1, 2, and 3.

[0045] Example 2: Preparation of spherical (TaNbTiV)C high-entropy carbide powder and coating The other steps are the same as in Example 1, except that the raw material powder in the first step is: Ta2O5, Nb2O5, TiO2, V2O5, and carbon black. The mass ratio of the raw material powder is Ta2O5: Nb2O5: TiO2: V2O5: C = 32.18: 19.36: 11.63: 13.24: 23.59. The main process parameters for preparing high-entropy carbide coatings by atmospheric plasma spraying are: power 40 kW, main gas (Ar) flow rate 90 L / min, auxiliary gas (H2) flow rate 100 L / min, and powder delivery gas flow rate 0.4 m³ / min. 3 The spraying speed was 100 mm / h, and the resulting coating thickness was approximately 200 μm. After sieving, spherical (TaNbTiV)C powder with a particle size distribution of 45–65 μm was obtained, with a Hall flow rate of 41.3 s / 50 g and a bulk density of 2.82 g / cm³. 3XRD analysis of the powder revealed a single rock salt phase. Image analysis showed the coating density to be 98% and the porosity to be 2%. Nanoindentation testing showed the coating's nanohardness to be 16.63 GPa. Tribological testing (under the same conditions as Example 1) showed the coating's coefficient of friction to be 0.38 and its wear rate to be 5.6 × 10⁻⁶. -7 mm 3 / (N·m). After plasma ablation test (2400 ℃, 120 s), the linear ablation rate of the coating was -1.47 μm / s, and the mass ablation rate was 0.67 mg / s.

[0046] Example 3: Preparation of spherical (TaNbTiVZr)C high-entropy carbide powder and coating The other steps are the same as in Example 1, except that the raw material powder in the first step is: Ta2O5, Nb2O5, TiO2, V2O5, ZrO2, and carbon black. The mass ratio of the raw material powder is Ta2O5: Nb2O5: TiO2: V2O5: ZrO2: C = 26.12: 15.71: 9.44: 10.75: 14.57: 23.41. The main process parameters for preparing high-entropy carbide coatings by atmospheric plasma spraying are: power 42 kW, main gas (Ar) flow rate 100 L / min, auxiliary gas (H2) flow rate 120 L / min, and powder delivery gas flow rate 0.4 m³ / min. 3 The spraying speed was 1 / h, and the spraying distance was 100 mm. The resulting coating thickness was approximately 300 μm. The wear resistance of the resulting coating was similar to that of Example 1, but the resistance to plasma ablation was slightly reduced.

[0047] Example 4: Preparation of spherical (TaNbTiVW)C high-entropy carbide powder and coating The other steps are the same as in Example 1, except that the raw material powder in the first step is: Ta2O5, Nb2O5, TiO2, V2O5, WO3, and carbon black. The mass ratio of the raw material powder is Ta2O5: Nb2O5: TiO2: V2O5: WO3: C = 23.00: 13.84: 8.32: 9.47: 24.13: 21.24. The main process parameters for preparing high-entropy carbide coatings by atmospheric plasma spraying are: power 40kW, main gas (Ar) flow rate 100 L / min, auxiliary gas (H2) flow rate 100 L / min, and powder delivery gas flow rate 0.4 m³ / min. 3 The spraying speed was 1 / h, and the spraying distance was 100 mm. The resulting coating thickness was approximately 300 μm. The wear resistance and ablation resistance of the resulting coating were similar to those in Example 1.

[0048] Example 5: Preparation of spherical (TaNbTiVZrMo)C high-entropy carbide powder and coating The other steps are the same as in Example 1, except that the raw material powder in the first step is: Ta2O5, Nb2O5, TiO2, V2O5, ZrO2, MoO3, and carbon black. The mass ratio of the raw material powder is Ta2O5: Nb2O5: TiO2: V2O5: ZrO2: MoO3: C = 21.41:12.88: 7.75: 8.81: 11.94: 13.95: 23.26. The main process parameters for preparing high-entropy carbide coatings by atmospheric plasma spraying are: power 40 kW, main gas (Ar) flow rate 100 L / min, auxiliary gas (H2) flow rate 100 L / min, and powder delivery gas flow rate 0.4 m³ / min. 3 The spraying speed was 1 / h, and the spraying distance was 100 mm. The resulting coating thickness was approximately 300 μm. The wear resistance and ablation resistance of the resulting coating were improved compared to Example 1.

[0049] Example 6: Preparation of spherical (TaNbTiVZrW)C high-entropy carbide powder and coating The other steps are the same as in Example 5, except that the raw material powder in the first step is: Ta2O5, Nb2O5, TiO2, V2O5, ZrO2, WO3, and carbon black. The mass ratio of the raw material powder is Ta2O5: Nb2O5: TiO2: V2O5: ZrO2: WO3: C = 19.73:11.87: 7.13: 8.12: 11.00: 20.71: 21.44. The main process parameters for preparing high-entropy carbide coatings by atmospheric plasma spraying are: power 40 kW, main gas (Ar) flow rate 100 L / min, auxiliary gas (H2) flow rate 100 L / min, and powder delivery gas flow rate 0.4 m³ / min. 3 The spraying speed was 1 / h, and the spraying distance was 100 mm. The resulting coating thickness was approximately 300 μm. The wear resistance and ablation resistance of the resulting coating were improved compared to Example 1.

[0050] To verify the performance advantages of the SiC / high-entropy carbide composite coating and the importance of the SiC transition layer in this invention, the following comparative examples were designed.

[0051] Comparative Example 1: (Single Principal Element Carbide) The substrate was graphite, and the pretreatment method involved roughening it with 100-mesh sandpaper. A SiC transition layer with a thickness of approximately 100 μm was then prepared on the treated substrate surface according to the method in Example 1. TiC powder was then sprayed onto the sandblasted SiC transition layer to obtain a SiC / TiC composite coating. The process parameters for preparing the TiC coating by atmospheric plasma spraying were: power 42 kW, main gas (Ar) flow rate 100 L / min, auxiliary gas (H2) flow rate 120 L / min, and powder feed gas flow rate 0.4 m³ / min. 3 / h, spraying distance 100 mm. The resulting coating thickness is approximately 300 μm.

[0052] Comparative Example 2: (Dual Principal Carbides) The substrate was graphite, and the pretreatment method involved roughening it with 100-mesh sandpaper. A SiC transition layer with a thickness of approximately 100 μm was prepared on the treated substrate surface according to the method in Example 1. ZrC-TiC powder was then directly sprayed onto the sandblasted SiC transition layer to obtain a SiC / (ZrTi)C composite coating. The process parameters for preparing the (ZrTi)C coating by atmospheric plasma spraying were: power 42 kW, main gas (Ar) flow rate 100 L / min, auxiliary gas (H2) flow rate 120 L / min, and powder delivery gas flow rate 0.4 m³ / min. 3 / h, spraying distance 100mm. The resulting coating thickness is approximately 300 μm.

[0053] Comparative Example 3: (Direct spraying of multi-principal carbide) The substrate was graphite, and the pretreatment method involved roughening it with 100-mesh sandpaper. A SiC transition layer with a thickness of approximately 100 μm was prepared on the treated substrate surface according to the method in Example 1. ZrC-TiC-NbC-Cr3C2-V8C7 spherical powder was then directly sprayed onto the sandblasted SiC transition layer to obtain a SiC / (ZrNbTiCrV)C composite coating. The process parameters for preparing the (ZrNbTiCrV)C coating by atmospheric plasma spraying were: power 42 kW, main gas (Ar) flow rate 100 L / min, auxiliary gas (H2) flow rate 120 L / min, and powder feed gas flow rate 0.4 m³ / min. 3 / h, spraying distance 100 mm. The resulting coating thickness is approximately 300 μm.

[0054] Comparative Example 4 (without SiC transition layer) The substrate was graphite, and the spherical (TaNbTiVMo)C powder obtained in Example 1 was directly sprayed onto the substrate surface. The process parameters used for atmospheric plasma spraying were the same (power 40 kW, main gas Ar flow rate 90 L / min, auxiliary gas H2 flow rate 100 L / min, powder delivery gas flow rate 0.4 m³ / min). 3 / h, spraying distance 100 mm). The resulting coating thickness was less than 50 μm, and it peeled off severely, indicating that the SiC transition layer is crucial to the bonding strength.

[0055] Matters not covered in this invention are common knowledge.

Claims

1. A method for preparing spherical high-entropy carbide powder, characterized in that, The method includes the following steps: S1. Raw material preparation: Select the corresponding metal oxide powder according to the chemical formula of the target substance MC, and calculate the weight according to the equimolar ratio of metal atoms; in addition, determine the required carbon source mass according to the sum of the molar amounts of the corresponding metal carbides; finally, mix the metal oxide powder and carbon source to obtain the raw material powder. Wherein, M is at least four of the metals Ta, Hf, Nb, Ti, V, Mo, Zr and W; and the molar ratio of each metal element is the same; the carbon source is selected from at least one of carbon black, graphite and carbon nanotubes; S2. Ball milling and mixing: The raw material powder prepared in step S1 is added to a ball mill and mixed to obtain ductile iron powder; S3. Carbothermic reduction synthesis: The inside of the crucible is lined with graphite paper, and the mixed spherical graphite powder is loaded into the crucible; graphite paper is then placed on top of the powder; a 5-10 mm layer of graphite powder is then laid on the graphite paper, and finally a layer of activated carbon with a particle size of 1-5 mm is placed on top, with a covering thickness of 10-20 mm; after the crucible is covered, it is placed in a box furnace and heated at 1500-1800 ℃ for 0.5-2 hours. After the reaction is completed, it is cooled with the furnace to obtain high-entropy carbide powder. S4. Crushing and refining: The high-entropy carbide powder obtained in step S3 is ball-milled for 1-2 hours using intermittent ball milling to obtain refined high-entropy carbide powder; S5. Spray granulation: The refined powder is mixed with deionized water, binder and dispersant in proportion to form a slurry, and then the slurry is granulated by spray drying to obtain spherical high-entropy carbide powder. The binder is a 1-3 wt.% sodium carboxymethyl cellulose solution or a polyvinyl alcohol aqueous solution, and the dispersant is sodium polyphosphate, with a mass of 1-2 wt.% of the total powder mass; the solid content of the slurry is 30-40 wt.%; the spray drying inlet temperature is 240-260 ℃, and the outlet temperature is 100-120 ℃.

2. The method for preparing spherical high-entropy carbide powder as described in claim 1, characterized in that, The obtained spherical high-entropy carbide powder is regularly spherical or nearly spherical, with a particle size D50 adjustable from 30 to 70 μm, uniform particle size distribution, Hall flowability <45s / 50 g, and loose packing density ≥2.4 g / cm³. 3 It has a uniform composition and is a single rock salt structure phase.

3. The method for preparing spherical high-entropy carbide powder as described in claim 1, characterized in that, The metal oxide powder has a particle size of 0.001~10 μm, and the carbon source has a particle size of 0.001 μm~10 μm.

4. The method for preparing spherical high-entropy carbide powder as described in claim 1, characterized in that, The metal oxide powder is the corresponding metal Ta2O5, HfO2, Nb2O5, TiO2, V2O5, MoO3, ZrO2 or WO3.

5. The method for preparing spherical high-entropy carbide powder as described in claim 1, characterized in that, In step S2, the ball-to-material ratio is 1~2:1, the rotation speed is 100~300 r / min, and the time is 1~3 hours; in step S3, the heating rate is 2~10 ℃ / min. In step S4, during intermittent ball milling, the machine is stopped for 5-15 minutes to cool down after every 15-25 minutes of grinding; the ball-to-material ratio is 2-5:1, and the rotation speed is 200-400 r / min.

6. A method for preparing a high-density SiC / high-entropy carbide composite coating, characterized in that, Includes the following steps: S6. Pretreatment of substrate before spraying: Roughen the surface of the substrate and grind it to a surface roughness Ra≈2~4 μm; The matrix material is graphite, carbon fiber reinforced carbon matrix composite, carbon fiber reinforced silicon carbide matrix composite, or silicon carbide fiber reinforced silicon carbide matrix composite. S7. Preparation of SiC transition layer: A pure silicon coating of 50~100 μm thickness is first deposited on the surface of the pretreated substrate by atmospheric plasma spraying; Then, a SiC transition layer is obtained using thermal spraying technology; S8. Preparation of high-entropy carbide coating: A high-entropy carbide ceramic coating is deposited on the SiC transition layer using thermal spraying technology, and the spray feed is the spherical high-entropy carbide powder described above; The thermal spraying technology mentioned is atmospheric plasma spraying or supersonic flame spraying.

7. The method for preparing the high-density SiC / high-entropy carbide composite coating as described in claim 6, characterized in that, In steps S7 and S8, atmospheric plasma spraying or supersonic flame spraying is used for deposition, and the substrate is preheated to 100~200 ℃ during spraying.

8. The method for preparing the high-density SiC / high-entropy carbide composite coating as described in claim 6, characterized in that, The atmospheric plasma spraying process parameters in step S7 include: current 450~550 A, voltage 60~80 V, argon flow rate 90~120 L / min, hydrogen flow rate 80~120 L / min, and powder delivery gas flow rate 0.1~0.3 m³ / min. 3 / h, spray gun distance from surface 50~100 mm; then, place the substrate specimen with pure silicon coating in a corundum crucible with graphite paper wrapped inside, completely cover the substrate in graphite powder and compact it; after covering the crucible with the lid, place the crucible in a box furnace and hold at 1450~1550 ℃ for 0.5~2 hours to carry out carburizing reaction. After the furnace cools to room temperature, take out the specimen, that is, a dense SiC transition layer is generated in situ on the substrate surface; after carburizing, the surface of the SiC layer is lightly sandblasted to increase its roughness Ra to 6~8 μm; In step S8, the atmospheric plasma spraying process includes: a current of 450~550 A, a voltage of 75~90 V, a main gas Ar flow rate of 80~130 L / min, an auxiliary gas H2 flow rate of 90~130 L / min, and a powder delivery gas flow rate of 0.3~0.6 m³ / min. 3 / h, spray gun distance from substrate 80~150 mm; coating thickness reaches 200~300 μm.

9. The method for preparing the high-density SiC / high-entropy carbide composite coating as described in claim 6, characterized in that, The thickness of the SiC transition layer is 50~100 μm, and the thickness of the high-entropy carbide ceramic coating is 200~700 μm.

10. The method for preparing the high-density SiC / high-entropy carbide composite coating as described in claim 6, characterized in that, The high-density SiC / high-entropy carbide composite coating has a density >95% and a porosity <5%.